Predictive factors for 1-year outcome of a cohort of patients with severe traumatic brain injury (TBI): Results from the PariS-TBI study. (August 2013) - Jourdan, C.; Bosserelle, V.; Azerad, S.; Ghout, I.; Bayen, E.; Aegerter, P.; Weiss, J. J.; Mateo, J.; Lescot, T.; Vigué, B.; Tazarourte, K.; Pradat-Diehl, P.; et al.
Abstract Objectives: To assess outcome and predicting factors 1 year after a severe traumatic brain injury (TBI). Methods: Multi-centre prospective inception cohort study of patients aged 15 or older with a severe TBI in the Parisian area, France. Data were collected prospectively starting the day of injury. One-year evaluation included the relatives-rating of the Dysexecutive Questionnaire (DEX-R), the Glasgow Outcome Scale–Extended (GOSE) and employment. Univariate and multivariate tests were computed. Results: Among 257 survivors, 134 were included (mean age 36 years, 84% men). Good recovery concerned 19%, moderate disability 43% and severe disability 38%. Among patients employed pre-injury, 42% were working, 28% with no job change. DEX-R score was significantly associated with length of education only. Among initial severity measures, only the IMPACT prognostic score was significantly related to GOSE in univariate analyses, while measures relating to early evolution were more significant predictors. In multivariate analyses, independent predictors of GOSE were length of stay in intensive care (LOS), age and education. Independent predictors of employment were LOS and age. Conclusions: Age, education and injury severity are independent predictors of global disability and return to work 1 year after a severe TBI.